(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the descriptive interpretation of the names of neologisms of the period of independence. On the example of ergonyms, the role of borrowings of the source language in the formation of names and promising ways of choosing a national name is studied. In the process of analysis, the names of trading places were considered as a separate system. Specific examples illustrate the essence of the name, important aspects of its formation as a sphere. It was also explained that new naming models in world practice are becoming the task of representatives of such areas as a linguist, marketer, psychologist and lawyer. Analyzed and commented on the opinions of linguists who conducted research on the topic of names. The reflection coefficient of neologism names in cross-sectoral studies was studied, and it was recognized that this criterion is determined by the ability of networks to perceive innovations. The requirements for the proper place of the name in the vocabulary are determined. It is proved that the created name can convey important information about the object or product that it names, fully meets the phonetic, lexical, morphological norms of the language.